Contemporary Issues in Industry 5.0 : Towards an AI Integrated Society - Päivi Aaltonen; Emil Kurvinen (Palgrave Macmillan, 2025)
‘Industry 5.0'was first described in 2020 by the European Commission to describe the next wave of technologies, including Virtual Simulation and Automated Robots, to impact businesses and individuals. It recognizes how these technologies can no more be counted as purely ‘future tech', but as realities that will begin to impact society as a whole. This open access book describes this new world as'Society 5.0'and explores the real impact of AI-enabled business on society. Beginning with a brief history of AI, the current terms, and its conceptual components, visualisation, data, and algorithms, this book then presents a collection of studies from leading scholars in the field of AI and Digital Business. The first section focuses on the immediate challenges and strategic changes that will be required for businesses to successfully adapt to this new reality. The second focuses on the opportunities of AI to businesses and society. And the final section includes chapters on the future and the possibilities and challenges that lie beyond Industry 5.0. It will be of great interest to scholars and students of innovation strategy and digital business, as well as all those engaged in research around cutting-edge technologies and their impact on society.